Effectiveness of Implementing the DRTA Strategy Based on P5 to Improve Reading Interest of Fifth-Grade Students - apfani, sry Apfani; Tulljanah, Rahmia; Ramadhini, Kurniati; Suryani, Ade Irma; Kharisma, Annisa; Ekawati, Ridania (Jurnal Kajian dan Pengembangan Umat, 2025)
This study aims to determine the effect of implementing the Directed Reading Thinking Activity (DRTA) strategy based on the Pancasila Student Profile (P5) on reading comprehension skills in integrated thematic learning for fifth-grade students at SD Negeri 07 Sikabu Munto, Pesisir Selatan. The study was motivated by the low reading comprehension abilities among students, indicated by limited concentration when reading, difficulty understanding text content, and challenges in drawing conclusions from passages. The research employed an experimental method with a posttest-only control design. The sample consisted of two classes: an experimental class taught using the P5-based DRTA strategy and a control class taught using conventional instruction. Reading comprehension data were obtained through a posttest, and the results were analyzed using normality tests, homogeneity tests, and an independent samples t-test. The results showed that the experimental group achieved a higher mean score (M = 82.5) compared to the control group (M = 72.3). The independent t- test indicated a significant difference between the two groups (t(48) = 3.27, p 0.01), confirming that students who received DRTA-based P5 instruction demonstrated significantly better reading comprehension skills. The P5-based DRTA strategy effectively guided students to make predictions, focus attention, verify understanding, and construct deeper meaning from texts. In conclusion, the P5-based DRTA strategy is effective for improving students’ reading